Financial management of fish and seafood processing enterprises in Vietnam during the COVID-19 pandemic - T. H. Pham (Вестник университета)
The article analyses the impact of the COVID-19 pandemic on the financial state of enterprises in the fish and seafood processing industry in Vietnam. The most important condition for maintaining stable development is effective financial management of the enterprise. During the pandemic, when demand decreased, this led to a reduction in supply. The state of imports and exports was difficult due to the lack of human resources due to the health situation, the closure of the country's borders. This circumstance has seriously affected production, and, consequently, the financial situation of fish and seafood processing enterprises. The paper concludes that the financial management system of these enterprises should be aimed at their effective use in the face of emerging problems. The author proposes solutions for increasing the financial resources of enterprises.